PENGARUH PENERAPAN GOOD GOVERNANCE TERHADAP KINERJA PENGELOLAAN KEUANGAN DESA PADA KECAMATAN SILIMAKUTA - Sirait, Sri Andika; Parhusip, Poltak Theodorus (Jurnal Ilmiah Akuntansi (JIMAT), 2023)
This study aims to determine the effect of the implementation of good governance on the performance of village financial management in Silimakuta sub-district. This study used primary data of 60 people from the village government apparatus of Sinar Baru and Purba Sinombah with the sampling technique used was purposive sampling. The data analysis techniques used are multiple linear regression analysis using the SPSS 22 program and hypothesis testing using t test and F test with a significance level of 5%. From the results of testing using SPSS, it is known that, the results of hypothesis testing with F test (simultaneous) show that the implementation of good governance has a significant effect on the performance of village financial management, this is obtained from the ttable > calculation, which is 16,680 > 3,156 and a significance value of 0.000 < 0.05. The results of hypothesis testing with a t test (partial) show that the variable of transparency application has a significant effect on the performance of village financial management, this is obtained from the ttable > tcal, which is 5,106 > 1,672 and a significance value of 0.002 < 0.05 , which means that if the implementation of the principle of transparency in village financial management will have a positive impact on governance and will increase the accountability of the village government, Then the performance of village financial management will improve for the better. The variable of the application of accountability has a significant effect on the performance of village financial management, this is obtained from the calculation of the ttable >, namely increasing trust and satisfaction with financial management by the village government, the performance of village financial management will improve for the better. Keywords: Good Governance, Transparency, Accountability, and Performance of Village Financial Management.